1992
DOI: 10.1042/bj2830759
|View full text |Cite
|
Sign up to set email alerts
|

Increases in intestinal glucose absorption and hepatic glucose uptake elicited by luminal but not vascular glutamine in the jointly perfused small intestine and liver of the rat

Abstract: 1. Previous studies have shown that an arterial-to-portal glucose concentration gradient may be an important signal for insulin-dependent net hepatic glucose uptake. It is not known whether intestinal factors also contribute to the regulation of hepatic glucose utilization. This problem was studied in a newly developed model which allows luminal perfusion of the small intestine via the pyloric sphincter and a combined vascular perfusion of the small intestine via the gastroduodenal artery and superior mesenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Glutamine is an important fuel for rapidly dividing cells, including those of the small intestinal mucosa. It has been suggested that glutamine accelerates hyperplasia following resection and enhances intestinal glucose and sodium absorption [68][69][70][71][72]. However, Vanderhoof et al [73] were unable to demonstrate a trophic effect with the addition of 5% glutamine to a chow diet following resection in the rat.…”
Section: Luminal Nutrients and Pancreatobiliary Secretionsmentioning
confidence: 99%
“…Glutamine is an important fuel for rapidly dividing cells, including those of the small intestinal mucosa. It has been suggested that glutamine accelerates hyperplasia following resection and enhances intestinal glucose and sodium absorption [68][69][70][71][72]. However, Vanderhoof et al [73] were unable to demonstrate a trophic effect with the addition of 5% glutamine to a chow diet following resection in the rat.…”
Section: Luminal Nutrients and Pancreatobiliary Secretionsmentioning
confidence: 99%
“…Providing parenteral feedings that contained this amino acid supported mucosal growth under a variety of conditions,2' including mucosal hypertrophy that occurred after extensive small-bowel resection.22 Other studies have documented improved bowel function, including absorption, when L-glutamine was provided by parenteral23 and/or enteral feedings. 24 Second, both animal and human studies have demonstrated that growth hormone, now available in recombinant form, stimulates intestinal growth25 and enhances transport ofnutrients across the small bowel. 26 Although we observed few significant clinical effects when these agents were administered alone, under the conditions of our study, enhanced absorption was observed when the agents were given together.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not possible that the action of the polyamines on glucose absorption is mediated via other hormones or the de-novo synthesis of SGLT1, because the response time is so short. Gardmann et al 21 reported that luminal glutamine upregulated glucose uptake from the small intestine within 2 min, although they did not measure SGLT1 protein. 21 Stümpel et al 7 indicated that an intra-arterial injection of glucagon 37 immediately stimulated glucose absorption in the rat intestine, and concluded that it exerted its actions via SGLT1.…”
Section: Discussionmentioning
confidence: 98%
“…Gardmann et al 21 reported that luminal glutamine upregulated glucose uptake from the small intestine within 2 min, although they did not measure SGLT1 protein. 21 Stümpel et al 7 indicated that an intra-arterial injection of glucagon 37 immediately stimulated glucose absorption in the rat intestine, and concluded that it exerted its actions via SGLT1. Therefore, a mechanism exists to activate glucose transporters rapidly.…”
Section: Discussionmentioning
confidence: 98%